2011
DOI: 10.1002/clen.201000182
|View full text |Cite
|
Sign up to set email alerts
|

Dye Removal from Colored Textile Wastewater by Poly(propylene imine) Dendrimer: Operational Parameters and Isotherm Studies

Abstract: Dye Removal from Colored Textile Wastewater by Poly(propylene imine) Dendrimer: Operational Parameters and Isotherm StudiesThis paper deals with the removal of textile dyes from aqueous solutions by poly (propylene imine) dendrimer (PPI). Direct red 80 (DR80), Acid Green 25 (AG25), Acid Blue 7 (AB7), and Direct Red 23 (DR23) were used as model dyes. The effects of operational parameters on dye removal such as dendrimer concentration, dye concentration, salt (inorganic anions), and pH have been studied at 258C.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
55
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 100 publications
(59 citation statements)
references
References 27 publications
1
55
0
Order By: Relevance
“…These groups produce hydrogen at acidic pH. Generally, an increase in the pH leads to a decrease in the sites in the positively charged dendrimer and thus, a decrease in the dye removal efficiency (19,20). In general for anionic dyes, adsorption capacity increases by reducing the pH of the solution while it is reverse for cationic dyes (20).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These groups produce hydrogen at acidic pH. Generally, an increase in the pH leads to a decrease in the sites in the positively charged dendrimer and thus, a decrease in the dye removal efficiency (19,20). In general for anionic dyes, adsorption capacity increases by reducing the pH of the solution while it is reverse for cationic dyes (20).…”
Section: Discussionmentioning
confidence: 99%
“…In the study of Ghaneian et al on the effect of adsorption of the Russian knapweed flower powderon the removal of RB19, the results showed that by increasing the adsorbent dose from 0.2 to 0.6 g/100 mL, removal efficiency increased from 72% to 82% (16). In a study by Hayati et al, G2 PPI dendrimer was used for the removal of dyes from textile wastewater, and the results indicated that increasing concentrations of dendrimers leads to increased dye removal and the optimal dendrimer concentration was 1.8 g/L (19). In another study on the adsorption of reactive red 198 by titanium dioxide nanoparticles, by increasing the adsorbent concentration, the adsorption efficiency of dye increased and the optimal adsorbent dosage was reported 1 g/L (25), which are consistent with the results reported by Yiyun and Jiepin (22).…”
Section: Discussionmentioning
confidence: 99%
“…However, the prominent role of ultrasound power on rapid uptake and quick establishment of equilibrium cannot be ignored. The efficiency of ultrasonic power in wastewater treatment could be due to hydrodynamic and thermal processes of acoustic cavitation which accelerate chemical process [53,[61][62][63][64][65][66][67][68]. It can be seen that the ultrasound-assisted approach greatly reduced the extraction time from 60 min to 15 min and can be concluded that this method is faster and more efficient than magnetic stirrer assisted method.…”
Section: Evaluation Of the Ls-svm Modelmentioning
confidence: 99%
“…Due to these harmful effects, the colored wastewaters must be appropriately treated before discharging into the water resources and ecosystem. Several processes including coagulation-flocculation, electro-coagulation, adsorption, advanced oxidation processes (O 3 /H 2 O 2 , H 2 O 2 /UV and photo-catalysis), flotation, membrane techniques (ultra-filtration, nanofiltration, and reverse osmosis), and biological degradation have been successfully applied for dyes removal from wastewaters [5,6,10,11,[13][14][15]. Despite a series of advantages, there are some disadvantages and limitations such as low removal efficiency, great electrical energy requirement, and high-cost operation for the various dye treatment methods [4,16].…”
Section: Introductionmentioning
confidence: 99%